Increased glucose synthesis in renal tubule fragments from hyperthyroid rats - Pimenta, W. P. [UNESP]; Silva Veiga, J. A. [UNESP] (Canadian Science Publishing, 1999)
Rates of glucose synthesis from several substrates were examined in renal tubule fragments from hyperthyroid rats. A hyperthyroid state was induced by daily intraperitoneal injections of thyroxine (T4) (100 μg/100 g body weight) for 14 days. At the end of the experimental period, plasma triiodothyronine and T4 levels were six and eight times higher, respectively, than initial values. Hyperthyroid rats gained less weight and had lower blood glucose despite an increased food intake. In both control and hyperthyroid rats, rates of glucose production by renal tubule fragments were higher with glutamine and glycerol than with lactate, alanine, or glutamate. T4 treatment induced a significant increase in the de novo glucose synthesis from all substrates, except glutamine. The highest percent increase was obtained with alanine (64%), compared with 31-40% for glutamate, lactate, and glycerol. The T4 treatment induced increase in glucose synthesis by renal tubule fragments suggests that renal gluconeogenesis contributes to enhance glucose production in hyperthyroidism.
Keywords: Alanine; Glutamate; Glutamine; Glycerol; Hyperthyroidism; Lactate; Rat; Renal gluconeogenesis; Renal tubule fragments